2021
DOI: 10.1002/sys.21597
|View full text |Cite
|
Sign up to set email alerts
|

A systems‐engineering approach to nation‐scale problems: Municipal solid waste management in Saudi Arabia

Abstract: The systems-engineering context of the solid waste disposal problem is discussed with a focus on the issues in Saudi Arabia. A methodology was developed for dividing the system of interest into a set of weakly-coupled sub-systems that interact with the narrow system of interest. A model of the narrow system of interest, in this case the municipal solid waste (MSW) system of Saudi Arabia, was then created and validated.The development of this mathematical model is described and is used to investigate a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Midgley et al [56] and Radwan et al [57] suggested that incineration is one of viable option to deal with municipal solid waste generated in Saudi Arabia. The United Arab Emirates (UAE) government intends to build a few incineration plants in order to reduce the volume of MSW produced and to reduce the landfill spaces required for the disposal [58].…”
Section: Municipal Solid Waste Incineration Ash (Mswia)mentioning
confidence: 99%
“…Midgley et al [56] and Radwan et al [57] suggested that incineration is one of viable option to deal with municipal solid waste generated in Saudi Arabia. The United Arab Emirates (UAE) government intends to build a few incineration plants in order to reduce the volume of MSW produced and to reduce the landfill spaces required for the disposal [58].…”
Section: Municipal Solid Waste Incineration Ash (Mswia)mentioning
confidence: 99%